Modelo preditivo para intervenção com injeção intravítrea de anti-VEGF em pacientes com edema macular diabético - Faria, Aline Roseane Queiroz de Paiva (2017)
Diabetic macular edema (DME) is the main cause of visual impairment in patients with diabetes mellitus. The most widely used treatment today is intravitreal injection (IIV) of anti-VEGF (vascular endothelial growth factor). Optical coherence tomography (OCT) is the gold-standard diagnostic test, however it is expensive and inaccessible. Some risk factors are strongly associated with development of DME and its response to treatment. There is few surveys that analyzes the impact and risk percentages of these factors in the probability of developing EMD and, therefore, in the necessity of early therapeutic intervention, which motivated the accomplishment of this research. This study aimed to achieve a Predictive Model to guide the decision in the early treatment with intravitreal injection in patients with EMD, by quantifying and ranking the risk factors impact on the chance of a diabetic patient need this therapy. It is a cross-sectional, observational, descriptive and analytical study. The data were collected at the Ophthalmology Department of the Lauro Wanderley University Hospital - UFPB and at the Hospital Visão, both in João Pessoa, and at the Genival Barbosa de Lucena Vision Center, located in Guarabira-PB, from July 2015 to September 2016. Individuals with type 1 or 2 diabetes and older than 18 years were included, after signing the informed consent form. The logistic regression model was used to obtain and adapt the predictive model and all the data were analyzed in statistical software R®, version 3.2.0. Eighty diabetic patients were evaluated: 57.5% had no indication of IIV and 42.5% needed this treatment. Of those who had EMD and needed anti-VEGF injection, the mean age was 60.65 years, 47.05% male and 52.94% female. In the group without macular edema, the mean age was 58.02 years, 26.06% male and 73.91% female. Among the individuals who had no indication of intravitreal injection of anti-VEGF, most had no mild retinopathy or non-proliferative diabetic retinopathy (NPDR) (69.56%). Among the patients who needed the treatment, the majority had severe NPDR or proliferative retinopathy (79.41%). Were identified as risk factors to EMD and intravitreal anti-VEGF: be retired (OR = 5.22, p-value0.05), had a personal history of diabetic retinopathy (OR = 20.27; P-value 0.006) and positive history for previous treatment with anti-VEGF (OR = 23.23; p-value 0.002). From the results of this study, we conclude that a diabetic individual has low visual acuity and presents these three factors, should be referred as soon as possible to the specialist, since he has a risk of presenting DME with need for anti-VEGF IIV, with 91.17% of accuracy. In summary, an evaluative and predictive model was proposed to serve as a supporting tool in therapeutic decision, mainly to the non-retinal physician, to refer to the specialist the patients with diabetic retinopathy and its main cause of low visual acuity - diabetic macular edema - to early diagnosis and treatment, which may be decisive to preventing irreversible visual loss in these patients.